2019
DOI: 10.1088/2058-9565/ab5e4f
|View full text |Cite
|
Sign up to set email alerts
|

Spectral signatures of non-thermal baths in quantum thermalization

Abstract: We show that certain coherences, termed as heat-exchange coherences, which contribute to the thermalization process of a quantum probe in a repeated interactions scheme, can modify the spectral response of the probe system. We suggest to use the power spectrum as a way to experimentally assess the apparent temperature of non-thermal atomic clusters carrying such coherences and also prove that it is useful to measure the corresponding thermalization time of the probe, assuming some information is provided on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…The theoretical modeling of such devices usually involves the system in contact with equilibrium uncorrelated baths at different temperatures. However, some papers have generalized this picture to nonequilibrium reservoirs [14][15][16][17][18][19][20][21], including the case of the Otto engine in contact with squeezed reservoirs [22][23][24][25], which can lead to efficiencies and performances beyond the Otto and Carnot limit. This conclusion, obviously, does not take into account the cost of maintaining a nonequilibrium reservoir which is then considered as a free resource but shows how to best employ these resources (see also Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical modeling of such devices usually involves the system in contact with equilibrium uncorrelated baths at different temperatures. However, some papers have generalized this picture to nonequilibrium reservoirs [14][15][16][17][18][19][20][21], including the case of the Otto engine in contact with squeezed reservoirs [22][23][24][25], which can lead to efficiencies and performances beyond the Otto and Carnot limit. This conclusion, obviously, does not take into account the cost of maintaining a nonequilibrium reservoir which is then considered as a free resource but shows how to best employ these resources (see also Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [121] showed that coherences in the bath can cause a thermalization to an apparent temperature which could be spectroscopically inferred [121].…”
Section: Non-equilibrium Quantum Thermodynamics: State Of the Artmentioning
confidence: 99%
“…Temperature is clearly defined only for systems in thermodynamic equilibrium. Nevertheless, many definitions of temperature have been shown to be useful in nonequilibrium situations [29][30][31][32][33][34][35][36][37].…”
Section: B Temperaturementioning
confidence: 99%